PENGARUH KEPEMIMPINAN, KONDISI KERJA DAN FASILITAS TERHADAP KEPUASAN KERJA PEGAWAI RUMAH SAKIT UMUM MAYJEN H.A. THALIB - Fadli Anugrah; Deky Hamdani; Rio Baviga (LP2M Universitas Bina Bangsa, 2024)
This study aims to examine leadership, working conditions, and facilities on job satisfaction of general hospital employees Mayjen H.A. Thalib. While the sample in this study were general hospital employees Mayjen H.A. Thalib which amounted to 34 respondent. Data collection techniques in this study are primary data collected through the distribution of questionnaires to respondents. This research method uses qualilative methods, while the analytical technique used is multiple linear regression analysis, t test, f test, and coefficient of determination test. Partially there is an influence between learership (X!) on job satisfaction (Y) in public hospital Mayjen H.A. Thalib evidenced by the value of t arithmetic > t table t value where the magnitude of the influence of leardership on job satisfaction of general hospital employees Mayjen H.A. Thalib by 17,4%. There is a positive and sifnificant effect between working condition (X2) partially on job satisfaction (Y) at the general hospital Mayjen H.A. Thalib was proven by the value of t count = 2,872% (t tabel 2,042%) with a significant = 0,007% (significant < 0,050%). Where the effect of working conditions on job satisfaction of general hospital employees Mayjen H.A. Thalib of 20. 04%. There is a positive and significant effect between facilities (X3) partially on job satisfaction (Y) at the general hospital Mayjen H.A. Thalib evidenced by the value of t count = 2.224 (t table > 2.042) with a significant value = 0.034 (significant < 0.050). the magnitude of the influence of facilities on job satisfaction of Mayjen H.A.Thalib general hospital employees. Talib by 5.8%. there is a simultaneous influence between leadership (X1), working condition (X2), and facilities (X3) on job satisfaction (Y) which is 43.3%. while the side 56.7% is influenced by other variables not examined in this study